Impact of national introduction of ten-valent pneumococcal conjugate vaccine on invasive pneumococcal disease in Bangladesh: Case-control and time-trend studies. Issue 40 (24th September 2021) - Baqui, Abdullah H.; Koffi, Alain K.; McCollum, Eric D.; Roy, Arunangshu D.; Chowdhury, Nabidul H.; Rafiqullah, Iftekhar; Ahmed, Zabed B.; Mahmud, Arif; Begum, Nazma; Ahmed, Salahuddin; Khanam, Rasheda; Harrison, Meagan; et al.
Abstract: Background: Bangladesh introduced the ten-valent pneumococcal conjugate vaccine (PCV10) into its national immunization program in March 2015 creating an opportunity to assess the real-world impact of PCV on invasive pneumococcal disease (IPD). Methods: Between January 2014 and June 2018, children aged 3–35 months in three rural sub-districts of Sylhet district of Bangladesh were visited every two months to collect morbidity and care-seeking data. Children attending sub-district hospitals with pneumonia, meningitis, or sepsis were assessed for IPD after obtaining informed consent. Blood and cerebrospinal fluid were collected from enrolled children to isolate pneumococcus using culture and molecular test. Children who were age-eligible to receive the PCV and had pneumococcus isolated were enrolled as cases. Four age and sex-matched clinic and community controls were selected for each case within one to two weeks of case identification. Data on immunization status and confounders were collected. PCV coverage was estimated using vaccine coverage surveys. Case-control and incidence trend analyses were conducted to assess the impact of PCV on IPD. Results: The community cohort yielded 217, 605 child years of observations and 154, 773 sick child-visits to study hospitals. Pneumococcus was isolated from 44 children who were age-eligible to receive PCV; these children were enrolled as cases. The cases were matched with 166 community- and 150 clinic-controls. The matched case-control analyses using community-controls showed 83% effectiveness (95% CI: 1.57–97.1%) and clinic controls showed 90% effectiveness (95% CI: −26.0% to 99.1%) of PCV in preventing IPD. Incidence trend analysis estimated vaccine effectiveness at 80.1% (95% CI: 38.4, 93.6). Conclusion: PCV in this pediatric population in Bangladesh was highly effective in preventing IPD.